Pancasila sebagai Sistem Etika Politik dan Etika Pemerintahan di Indonesia - Wahyu Trisno Aji; Mig Irianto Legowo (Universitas Palan, 2024)
The study aims to examine Pancasila as an ethical system in politics and government in Indonesia. Pancasila, which consists of five principles, is not only the foundation of the state but also a moral guideline that directs political and governmental behavior. This study uses a qualitative type of library research with a descriptive approach, which is a type of research that focuses on a phenomenon with data obtained in the form of literature that is naturally described in the form of words or writing. The results of the study obtained are in the context of political ethics, Pancasila functions as a moral identity that guides citizens and the government to act in accordance with ethical principles that are fair, wise, and in accordance with the values ​​of humanity, unity, and people's sovereignty. The implementation of political ethics based on Pancasila ensures that political actions are not only focused on power, but also morally and socially responsible to society. In government, Pancasila is the main guideline that ensures that the government acts for the welfare of all Indonesian people, by respecting the values ​​of humanity, justice, and unity. Every decision and policy taken by a leader must reflect the values ​​contained in Pancasila, such as divinity, humanity, democracy, and social justice. Pancasila is not only the basis of the country's constitution, but also an ethical system that guides the government in carrying out its duties with integrity, morality, and commitment to the interests of the people and the state.